Psychometric Properties of the Spanish Version of the Pain Anxiety Symptoms Scale-20. - López-Martínez, Alicia Eva; Esteve-Zarazaga, Rosa; Ruiz-Párraga, Gema Teresa; Rueda-Serrano, Carmen; Serrano-Ibáñez, Elena Rocío; Ramírez-Maestre, María del Carmen (Colegio Oficial de Psicólogos del Principado de Asturias, 2021)
Background: The PASS-20 is a general measure of pain-related anxiety and fear. The aim of the present study was to adapt the questionnaire for use in Spanish-speaking populations. Methods: Sample 1 comprised 216 individuals with chronic spinal pain (114 women and 102 men); sample 2 comprised 85 individuals with acute spinal pain (62 women and 23 men). The dimensionality of the PASS-20-SV items was evaluated using Exploratory Factor Analysis and an optimal implementation of Parallel Analysis (robust maximum likelihood). Data from sample 1 was used to analyse internal consistency and convergent validity. Estimated test-retest stability and predictive validity were based on data from the sample 2 participants, who completed the first administration (T1) and a second administration (T2, 6 months later). Results: The PASS-20-SV comprises two factors: pain-related anxiety and apprehension, and pain-related fear and avoidance. It has good to excellent reliability and adequate testretest stability. The results support its convergent and predictive validity. Conclusions: The Spanish Version of the PASS-20 is a valid, reliable measure of pain-related anxiety and pain-related fear in Spanish-speaking patients.
Psicothema es una revista de acceso abierto lo que significa que todo el contenido está a disposición de cualquier usuario o institución sin cargo alguno. Los usuarios pueden leer, descargar, copiar, distribuir, imprimir, buscar, o realizar enlaces a los textos completos de esta revista sin pedir permiso previo al editor o al autor, siempre y cuando la fuente original sea referenciada.
https://www.psicothema.com/NormasPublicacion2025.pdf: Psicothema permite el autoarchivo de la versión preprint, post-print y la versión editorial (inmediatamente después de la publicación)
Keywords: Dolor - Aspectos psicológicos; Psicometría; Pain anxiety; Fear of pain; PASS-20; Assessment; Psychometric properties